Encyclopedia of Life Sciences 2017
DOI: 10.1002/9780470015902.a0020109.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Signalling in Plants

Abstract: Nitric oxide (NO) is a small simple molecule, but one which is instrumental in cell signalling in a range of organisms including plants. It is a gas, often found in the form of a radical. It is produced in cells in an orchestrated manner, usually by dedicated enzymes and often following stress. It leads to numerous responses. In plants it is involved in seed germination, seedling development, stomatal responses, senescence and protection against pathogens, so is an instrumental signalling molecule used through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Nitric oxide (NO), a ubiquitous signal molecule, plays important roles in different plant tissues and participates in a variety of physiological processes [13]. Many researchers observed that NO induced root development in Zea mays [14], and it also induced seed germination, seedling development, stomatal responses, senescence, flowering and protection against pathogens in different plant species [15][16][17][18][19][20]. NO production in plants has two pathways, including enzymatic pathway and non-enzymatic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO), a ubiquitous signal molecule, plays important roles in different plant tissues and participates in a variety of physiological processes [13]. Many researchers observed that NO induced root development in Zea mays [14], and it also induced seed germination, seedling development, stomatal responses, senescence, flowering and protection against pathogens in different plant species [15][16][17][18][19][20]. NO production in plants has two pathways, including enzymatic pathway and non-enzymatic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO), a ubiquitous signal molecule, plays important roles in different plant tissues and participates in a variety of physiological processes [13]. Many researchers observed that NO induced root development in Zea mays [14], and it also induced seed germination, seedling development, stomatal responses, senescence, flowering and protection against pathogens in different plant species [15][16][17][18][19][20]. NO production in plants has two pathways, including enzymatic pathway and nonenzymatic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO) acts as a key regulator in the expression of various genes involved in plant life activities (Arasimowicz & Florysza-Kwieczorek, 2007;Hancock et al, 2017) that not only affects a series of physiological processes but also plays a crucial role in signal transduction (Domingos et al, 2015). Liu (2016), Liu et al (2017) found that NO fumigation used for pest control could improve the postharvest quality of fresh products.…”
mentioning
confidence: 99%